Women, the femenine and Theatre: Notes for a reading from the gender perspective - Galindo, Maria Fernanda (UNIVERSIDAD DE SONORA, 2021)
Starting off from Linda Nochlin’s famous analysis of women’s situation in visual arts in Why have there been no great women artists? (1971/2007), this article presents an overview of the situation of women in the performing arts and theatre in Sonora. After the discussion of concepts such as ‘the feminine’ and ‘gender’, it focuses, in a second step, on the active role of women in theatrical production and acting in the region. This article thus understands itself as a first step for future investigations analyzing the Sonoran theater scene from the perspective of gender. Keywords: